التمثيل الخرائطي لمحصول القمح في محافظة صلاح الدين باستخدام خريطة الدزيمترية ونطم المعلومات الجغرافية - حماد، عبدالرزاق صالح; الجواري، مهند فالح كزار شنون; البياتي، إسماعيل فاضل خميس مصطفى (جامعة تكريت - كلية الآداب, 2021)
يعد الإنتاج الزراعي لمحصول القمح الدعامة الأساسية للبنيان الاقتصادي والاجتماعي للسكان، ويمثل العصب الحساس للنشاط الاقتصادي، وتزداد أهميته باعتباره مهنة يرتبط بها وبأنشطتها المتباينة أكثر من نصف عدد السكان في منطقة الدراسة، سواء في الإنتاجي والتسويقي للزراعة، ويساهم الإنتاج الزراعة في نمو سكان المستوطنات البشرية وتوزيعهم، إذ إن التفاعل بين الإنتاج الزراعي والسكان متبادل مكانيا وزمانيا، ويتناول البحث موضوع تطبيقات في الخرائط (الديزيمترية) ونظم المعلومات الجغرافية، لرسم الخرائط الديزيمترية من خلال تضمين معلومات مكانية ووصفية لمتغيرات إنتاج القمح في محافظة صلاح الدين، والذي يهدف إلى معالجة البيانات الإنتاجية، وعند تطبيق التحليلات نحصل على خريطة جديدة تمثل تباين الإنتاج في منطقة الدراسة، وهى ما تسمى بالخرائط الديزيمترية. وأتبعت الدراسة المنهج الاستقرائي منهجا للدراسة، متخذا من وسائل وتقنيات القياس الكمي والإحصاء ومعطيات نظم المعلومات الجغرافية أداة للبحث والدراسة.
The agricultural production of the wheat crop is the mainstay of the economic and social structure of the population. It represents the sensitive nerve of economic activity, and it is more important as a related profession and its diverse activities in more than half of the population in the study area, both in production and marketing of agriculture. The interaction between agricultural production and population is spatially and temporally interrelated. The research deals with applications in maps and GIS for dithering, including the inclusion of spatial information and the descriptive variables of wheat production in Saladin Governorate, which aims at processing the production data. When applying the analyzes we obtain a new map representing the variation of production in the study area, which is called Dasymetric maps. The study followed the inductive method of study methodology, taking the means and techniques of quantitative measurement, statistics and GIS data as a tool for research and study.
Keywords: المحاصيل الزراعية -- التكنولوجيا الجغرافية -- العراق